Meraih Kesuksesan Keuangan: Meneliti Ukuran Perusahaan, Struktur Modal, dan Kebijakan Utang pada Perusahaan Manufaktur - Mulyadi, Olandari; Suryadi, Dodi; Permata Sari, Putri Intan; Puspita Sari, Yosi (Universitas Medan Area, 2023)
This article analyzes the influence of Company Size and Capital Structure on Financial Performance with Debt Policy as an Intervening Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) for the 2016-2020 period. This research focuses on the financial performance of 330 manufacturing companies selected using the purposive sampling method. The analysis was carried out using SPSS 25. The results of the research show that Company Size and Capital Structure have a partial effect on Debt Policy, and Company Size and Capital Structure also have a partial effect on Financial Performance. However, Debt Policy does not have a significant effect on Financial Performance. In addition, mediation of Debt Policy on the influence of Company Size on Financial Performance does not occur, while mediation of Debt Policy on the influence of Capital Structure on Financial Performance can occur